Investigation on the influence of wood pellets on the reactivity of coke with CO2 and its microstructure properties. (1st February 2022) - Kieush, Lina; Schenk, Johannes; Pfeiffer, Andreas; Koveria, Andrii; Rantitsch, Gerd; Hopfinger, Horst
Highlights: Pellets within the coke structure have a local influence, but the general influence in determining the properties of the resulting coke. Raman results do not have significant parameter changes for both coke and biocoke. Interlayer spacing of carbon crystallite has a strong line correlation with CRI and CSR values. Crystallite height of cokes and biocokes increasing very slightly with rising the carbonization temperature from 950 °C to 1100 °C. Abstract: Adding 5 mass% wood pellets in a coal blend affects the reactivity with CO2 and microstructural properties of the coke at different final coking temperatures of 950 and 1100 °C. A correlation between coke reactivity index (CRI) and BET specific surface area was found. The reactivity of coke and biocoke decreases with a decrease in the specific surface area, as well as with an increase in the carbonization temperature. Raman spectroscopy results indicate that the higher carbonization temperature of biocoke mitigates the effect of 5 mass% of biomass addition. The X-ray diffraction-based interlayer spacing of carbon crystallite (d002 ) decreases slightly with increasing carbonization temperature, and crystallite height (Lc ) increases with rising coking temperature for both coke and biocoke. Additionally, the lower the d002 value, the lower the CRI of the cokes and biocokes. A good correlation between CRI and d002 is observed. Carbon crystallite width (La ) values increased with a rising carbonization temperature, indicating the intensive growth of carbon crystallites in all directions. However, these values for biocokes are lower due to the presence of charcoal particles.